Motor Timing and Covariation with Time Perception: Investigating the Role of Handedness - O’Regan, Louise; Spapé, Michiel M.; Serrien, Deborah J. (Frontiers in Behavioral Neuroscience, 2017)
Time is a fundamental dimension of our behaviour and enables us to guide our actions and to experience time such as predicting collisions or listening to music. In this study, we investigate the regulation and covariation of motor timing and time perception functions in left- and right-handers who are characterised by distinct brain processing mechanisms for cognitive-motor control. To this purpose, we use a combination of tasks that assess the timed responses during movements and the perception of time intervals. The results showed a positive association across left- and right-handers between movement-driven timing and perceived interval duration when adopting a preferred tempo, suggesting cross-domain coupling between both abilities when an intrinsic timescale is present. Handedness guided motor timing during externally-driven conditions that required cognitive intervention, which specifies the relevance of action expertise for the performance of timed-based motor activities. Overall, our results reveal that individual variation across domain-general and domain-specific levels of organisation plays a steering role in how one predicts, perceives and experiences time, which accordingly impacts on cognition and behaviour.